2004
DOI: 10.1073/pnas.0401595101
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal domain of DNA gyrase A adopts a DNA-bending β-pinwheel fold

Abstract: DNA gyrase is unique among enzymes for its ability to actively introduce negative supercoils into DNA. This function is mediated in part by the C-terminal domain of its A subunit (GyrA CTD). Here, we report the crystal structure of this Ϸ35-kDa domain determined to 1.75-Å resolution. The GyrA CTD unexpectedly adopts an unusual fold, which we term a ␤-pinwheel, that is globally reminiscent of a ␤-propeller but is built of blades with a previously unobserved topology. A large, conserved basic patch on the outer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
273
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(291 citation statements)
references
References 62 publications
17
273
1
Order By: Relevance
“…Together, these results suggested that the DNA binding properties of these two prokaryotic enzymes are very different. It has been proposed that, with the help from GyrA-CTD, a continuous stretch of DNA can be wrapped by DNA gyrase to generate a (ϩ) supercoil-like intramolecular DNA cross-over to facilitate subsequent duplex passage reaction that produces net (Ϫ) supercoils in DNA (28,30,32). Consistent with its predicted catalytic function, deletion of GyrA-CTD converted DNA gyrase into a conventional type IIA Topo (26).…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Together, these results suggested that the DNA binding properties of these two prokaryotic enzymes are very different. It has been proposed that, with the help from GyrA-CTD, a continuous stretch of DNA can be wrapped by DNA gyrase to generate a (ϩ) supercoil-like intramolecular DNA cross-over to facilitate subsequent duplex passage reaction that produces net (Ϫ) supercoils in DNA (28,30,32). Consistent with its predicted catalytic function, deletion of GyrA-CTD converted DNA gyrase into a conventional type IIA Topo (26).…”
mentioning
confidence: 69%
“…Recently, the crystal structure of GyrA-CTD from Borrelia burgdorferi has been determined (30). Although the structure was globally reminiscent of a six-bladed ␤-propeller as predicted (25), GyrA-CTD folds with a novel topology and was alternatively termed to adopt a ␤-pinwheel fold (30).…”
mentioning
confidence: 99%
“…Previous studies with human and bacterial topoisomerases (19)(20)(21)(25)(26)(27)(28) suggest that the type II enzyme utilizes two distinct mechanisms to recognize the handedness of DNA supercoils. It has been proposed that the ability of some type II enzymes, such as human topoisomerase IIα and E. coli topoisomerase IV, to distinguish supercoil geometry during DNA relaxation is mediated by elements in the variable C-terminal domain (19,(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…However, several recent studies suggest that this portion of the protein plays an intriguing and important role in the recognition of DNA geometry [59][60][61][62][63][64][65]. As such, it may impart unique attributes, such as the ability to supercoil DNA [59][60][61] or act in front of replication forks [62,64], to specific type II enzymes. Unfortunately, no structural information is available for the C-terminal domain of any eukaryotic type II enzyme at the present time.…”
Section: Topoisomerase II Domain Structurementioning
confidence: 99%
“…In contrast, topoisomerase IIβ, which is not believed to play a role in DNA replication, relaxes positive and negative superhelical twists at similar rates [62]. On the basis of amino acid sequence comparisons between the two human topoisomerase II isoforms, as well as studies on bacterial and viral type II enzymes [59][60][61]65], it has been proposed that the ability to discern the geometry of DNA supercoils during relaxation resides in the C-terminal domain of human topoisomerase IIα.…”
Section: Effects Of Dna Supercoiling On Topoisomerase Ii-mediated Dnamentioning
confidence: 99%